Assessing The Impact of Capital Structure on Firm Value: A Quantitative Study of Financial Ratios and Stock Prices of Nigeria Food and Beverage Companies - Adamu, Ishiaka; Hamidah, Hamidah (The Indonesian Journal of Accounting Research, 2023)
This article evaluates the impact of capital structure (CS) on firm value (FV) in Nigeria's food and beverage sector. A quantitative research approach is employed, focusing on the association between financial ratios (debt to equity (DER), return on asset (ROA), current ratio, asset growth, and firm size) and stock prices as a proxy for firm value (FV). Panel data were sourced from financial statements of sixteen (16) publicly listed food and beverage companies in the Nigeria stock exchange from 2017 to 2021, and data were analyzed using statistical software. The descriptive statistics reveal the characteristics of the variables, showing variations in stock prices, ROA, current ratio, asset growth, firm size, and DER. Regression analysis using the random effects model demonstrates the significance of firm size on stock prices. At the same time, other variables (current ratio, ROA, debt to equity, and asset growth) are found to be insignificant. The research concludes that firm size has an unfavorable relevance impact on stock prices, showing that bigger firms tend to have lower stock prices. The findings contribute to the understanding of the connection between capital structure (CS) and firm value (FV) in the Nigerian food and beverage industry, providing insights for data-driven decision-making in the industry.